2012
DOI: 10.7314/apjcp.2012.13.5.1877
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Breast Cancer Metastasis Via PITPNM3 by Pachymic Acid

Abstract: Breast cancer metastasis is the most common cause of cancer-related death in women. Thus, seeking targets of breast tumor cells is an attractive goal towards improving clinical treatment. The present study showed that CCL18 from tumor-associated macrophages could promote breast cancer metastasis via PITPNM3. In addition, we found that pachymic acid (PA) could dose-dependently inhibit migration and invasion of MDA-MB-231cells ,with or without rCCL18 stimulation. Furthermore, evidence was obtained that PA could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 13 publications
2
22
0
Order By: Relevance
“…Also, metastasis is a multistep process involving cell detachment from the primary tumor, extravasation, and invasion to the secondary organ (Lv et al, 2011;Li et al, 2014). During the metastasis process, the oncogenes are activated and the tumor suppressor genes are inactivated, which may be responsible for breast cancer metastasis (Hong et al, 2012;Liu et al, 2013;Cao et al, 2014). Promoter hypermethylation of tumor suppressor genes is one of the ways to suppress its expression during the breast cancer metastasis (Lv et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, metastasis is a multistep process involving cell detachment from the primary tumor, extravasation, and invasion to the secondary organ (Lv et al, 2011;Li et al, 2014). During the metastasis process, the oncogenes are activated and the tumor suppressor genes are inactivated, which may be responsible for breast cancer metastasis (Hong et al, 2012;Liu et al, 2013;Cao et al, 2014). Promoter hypermethylation of tumor suppressor genes is one of the ways to suppress its expression during the breast cancer metastasis (Lv et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer metastasis is a major cause for the failure of treatment in women, making it crucial to identify proteins and signaling pathways involved in tumor cell dissemination (Hong et al, 2012;Truong et al, 2014). Also, metastasis is a multistep process involving cell detachment from the primary tumor, extravasation, and invasion to the secondary organ (Lv et al, 2011;Li et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Natural products have a critical role as an effective source of antitumor agents. Although PA is a promising bioactive molecule, which possesses an anti-carcinogenic activity in numerous types of cancer (12,17,18), the biological activity of PA in gastric cancer is poorly understood. In present study, the data indicated that PA was able to inhibit cell viability in a concentration-and time-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Poria cocos (also known as Wolfiporia extensa) is a medicinal mushroom in the Polyporaceae family that grows in pine trees and its sclerotium is widely used in traditional Asian medicine for its sedative, diuretic, digestive and tonic effects (6)(7)(8). Although the anticancer activity of polysaccharides extracted from P. cocos is associated with the stimulation of immune response and these polysaccharides significantly enhance immunopotentiation (9), triterpenes isolated from P. cocos have a direct inhibitory effect on cancer cells through a variety of mechanisms including inhibition of cell proliferation, induction of apoptosis and suppression of invasive behavior (10)(11)(12)(13)(14)(15)(16). However the effect of triterpenes from P. cocos against pancreatic cancer remains to be evaluated and the mechanism determined.…”
Section: Introductionmentioning
confidence: 99%